The protective effect of tangeretin and pomegranate separately and in combination on ethanol-induced acute gastric ulcer model - Susam, Solmaz; Ilhan, Nevin; Tedik, Fatma; Berk, Buket; Ilhan, Ayse Sebnem (Cukurova Univ, Fac Medicine, 2023)
Purpose: This study was designed to find an answer to the question, Is it beneficial to use pomegranate (POM) and tangeretin (TAN) separately or in combination, for the prevention of acute gastric ulcer?.Materials and Methods: The gastroprotective effect of tangeretin and pomegranate was determined by measuring the levels of the selected inflammatory cytokines [tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), IL-1(3 and IL-10], lipid peroxides, and enzymatic activities of antioxidants in gastric tissue samples.Results: When all groups are written as control, gastric ulcer, POM+EtOH, TAN+EtOH and POM+TAN+EtOH, respectively; IL-1(3 cytokine levels were measured as 0.147, 0.24, 0.228, 0.195 and 0.182 pg/g protein. IL-6 levels; 16,857, 25,923, 19,797, 18,838 and 17,896 pg/mg protein. TNF-alpha levels were 39,916, 49.97, 44,678, 41,673 and 40,844 pg/mg protein. Finally, IL-10 levels were measured as 33,496, 28,071, 29,693, 30,073 and 30,008 pg/mg protein. SOD activities were determined as 18,038, 13,731, 15,506, 14,439, and 15,943. CAT activities were 674,638, 639,964, 673,382, 664,691, and 671,203. Protein carbonyl levels were measured as 26,799, 40,30, 33,052, 34,579 and 32,79. Finally, MDA levels were found as 5,239, 9,814, 6,695, 5,771 and 5,836. Briefly, POM and TAN showed their antioxidant functions by decreasing the levels of malondialdehyde (MDA), and protein carbonyl and increasing the activity of superoxide dismutase (SOD) and catalase (CAT). And also, these protective agents exhibited their anti-inflammatory functions by decreasing the content of TNF-alpha, IL-6, and IL-1(3, and increasing the IL-10 levels.Conclusion: Tangeretin and pomegrenate have a potential gastroprotective effect against ethanol-induced acute gastric ulcer and that the combined treatment is more beneficial than the effect of POM or TAN alone. In addition, this effect is thought to be due to the fact that both selected flavonoids can show a synergistic effect, reducing the levels of inflammation parameters and increasing antioxidant levels.
Keywords: Gastric ulcer; pomegranate; tangeretin; ethanol; rat